Mechanisms of primordial follicle activation and new pregnancy opportunity for premature ovarian failure patients - Zhang, Tuo; He, Meina; Zhang, Jingjing; Tong, Yuntong; Chen, Tengxiang; Wang, Chao; Pan, Wei; Xiao, Ziwen (Frontiers in Physiology, 2023)
Primordial follicles are the starting point of follicular development and the basic functional unit of female reproduction. Primordial follicles are formed around birth, and most of the primordial follicles then enter a dormant state. Since primordial follicles are limited in number and can't be renewed, dormant primordial follicles cannot be reversed once they enter the growing state. Thus, the orderly occurrence of primordial follicles selective activation directly affects the rate of follicle consumption and thus determines the length of female reproductive lifespan. Studies have found that appropriately inhibiting the activation rate of primordial follicles can effectively slow down the rate of follicle consumption, maintain fertility and delay ovarian aging. Based on the known mechanisms of primordial follicle activation, primordial follicle in vitro activation (IVA) technique has been clinically developed. IVA can help patients with premature ovarian failure, middle-aged infertile women, or infertile women due to gynecological surgery treatment to solve infertility problems. The study of the mechanism of selective activation of primordial follicles can contribute to the development of more efficient and safe IVA techniques. In this paper, recent mechanisms of primordial follicle activation and its clinical application are reviewed.